Effects of carboxyamidotriazole-orotate on oncogenic phenotypes of mouse glioma-associated macrophage cell lines - MA Rui, YANG Li-xing, CHEN Qiu-xia, QIU Jia-xing, WANG Yu-cheng, JU Rui, GUO Lei (Jichu yixue yu linchuang, 2022)
Objective To explore regulation mechanism of carboxyamidotriazole-orotate (CTO) on oncogenic phenotype of mouse glioma-associated macrophages. Methods Bone marrow-derived macrophages(BMDMs) or RAW264.7 macrophages (tumor associated macrophages,TAMs) were prepared by super-culture of mouse glioma GL261 cells. The mRNA of TAMs oncogenic mediators was detected by qPCR. The oxygen consumption rate (OCR) of TAMs was measured by Seahorse bioenergy method. The protein level of hypoxia-inducible factor-1 α(HIF-1α), hypoxia-inducible factor-2 α (HIF-2α) and peroxisome proliferator-activated receptor (PPAR) co-activator factor-1 β (PGC-1β) in TAMs was detected by Western blot. Results CTO decreased M1-related mediators such as IL-1β, IL-6 and TNF-α(P＜0.001) and M2-related mediators such as IL-10, ARG-1 and TGF-β1(P＜0.001) in TAMs. CTO significantly down-regulated OCR in TAMs (P＜0.01); The protein level of HIF-1α and of HIF-2α in TAMs was down-regulated by CTO(P＜0.01),which was contrary to the effect of carboxycyanide-4-trifluormethoxyphenylhydrazone (FCCP),which in turn promoted mitochondrial oxygen consumption. CTO significantly reduced PGC-1β protein in TAMs (P＜0.001),an effect consistent with rotenone(RTN), a mitochondrial respiratory chain inhibitor. Conclusions A decreased oxidative phosphorylation down-regulates the expression of PGC-1β and destabilizes HIF-1α and HIF-2α, thus affects the production of several M1 and M2 phenotypes of carcinogenic mediators in TAMs, which may be a potential mechanism through which CTO improves the chemotherapy efficacy of glioblastoma.